Kinerja Fungsi Terminal Giri Adipura dalam Sistem Transportasi di Kabupaten Wonogiri - Nur Laila Fitriana; Galing Yudana; Winny Astuti (ARSITEKTURA, 2017)
Terminal is included in the transportation network system which functions as a place for passengers to take the bus and a place to drop the passengers. Terminal is also the element of spatial arrangement which influences the structure and system of a town’s movement. The development of Giri Adipura Terminal in Singodutan Village which was done from 2010 to 2014 is aimed to recover the performance of previous terminal and to develop the surrounding area. Phenomenon which was happened in Giri Adipura Terminal is there were still many passengers who were not utilizing the terminal function and the public transportations were not entering the terminal in order. This research was done to know the performance of Giri Adipura Terminal function in transportation system in Wonogiri Regency. The used research method was quantitative with deductive approach. The used analysis technique was scoring, by determined the parameter and indicator in each variabel. The result of scoring calculation from the performance of Giri Adipura Terminal function in transportation system in Wonogiri Regency was 9.33. Based on the performance of terminal function category, 9.33 score was in range of 6.68—9.35, so it was included in the average performance category. Thus, the performance of Giri Adipura Terminal function in transportation system in Wonogiri Regency has not reach a good performance yet and it needs some things which should be done to reach that performance. For the performance of each variable, variables which were in the good performance category were accessibility and traffic management. Meanwhile, variables which were in the average category were terminal service and transportation movement access. Keywords: performance, terminal function, transportation system